The prevalence of pediatric metabolic syndrome-a critical look on the discrepancies between definitions and its clinical importance - Reisinger, Carolin; Nkeh-Chungag, Benedicta N; Fredriksen, Per Morten; Goswami, Nandu (International Journal of Obesity, 2021)
The Metabolic Syndrome (MetS) describes the clustering of cardio-metabolic risk factors-including abdominal obesity, insulin resistance, elevated blood pressure, high levels of triglycerides, and low levels of high-density lipoproteins-that increase the risk for developing cardiovascular diseases and type 2 diabetes mellitus. However, a generally accepted definition of MetS in pediatric patients is still lacking. The aim was to summarize current prevalence data of childhood MetS as well as to discuss the continuing disagreement between different pediatric definitions and the clinical importance of such diagnosis. A systematic literature search on the prevalence of pediatric MetS was conducted. Articles that were published during the past 5 years (2014-2019), using at least one of four predetermined classifications (International Diabetes Federation, Cook et al., Ford et al., and de Ferranti et al.), were included. The search resulted in 1167 articles, of which 31 publications met all inclusion criteria. The prevalence of MetS ranged between 0.3 and 26.4%, whereby the rising number of children and adolescents with MetS partly depended on the definition used. The IDF definition generally provided the lowest prevalences (0.3-9.5%), whereas the classification of de Ferranti et al. yielded the highest (4.0-26.4%). In order to develop a more valid definition, further research on long-term consequences of childhood risk factors such as abdominal obesity, insulin resistance, hypertension, and dyslipidemia is needed. There is also a temptation to suggest one valid, globally accepted definition of metabolic syndrome for pediatric populations but we believe that it is more appropriate to suggest definitions of MetS that are specific to males vs. females, as well as being specific to race/ethnicity or geographic region. Finally, while this notion of definitions of MetS specific to certain subgroups is important, it still needs to be tested in future research.